Correlations between Placental Thickness and Neonatal Outcomes: A Detailed Analysis at 32 and 36 Weeks - Alka Agrawal; Prachi Shukla; Vivek Yonati; Sapna Ahlawat; Rinku Meena; Deepak Ahlawat; Neelesh Patel (Acta Medica International)
Introduction: The placenta helps in supporting the developing fetus by providing essential metabolic, immunological, endocrine, respiratory and nutritional functions. During pregnancy, the placenta grows in size to adequately support the needs of the developing fetus. Abnormalities in placental thickness (PT) can serve as an indicator of potential complications during pregnancy. Utilizing ultrasound technology to assess the thickness of the placenta throughout pregnancy, aiming to identify potential connections with fetal well-being, as well as other relevant factors. In addition, the objective is to establish reference charts for PT during 32 and 36 weeks of gestation. Materials and Methods: An bservational study at a Medical College and Hospital in India, from February 2023–2024, that included 400 patients. The thickness of the placenta was measured at 32 and 36 weeks in women who were referred for antenatal scans. Out of the 400 participants, 25 gave birth before reaching 36 weeks, while the remaining 375 were monitored until they reached 36 weeks. The thickness was categorized into three groups: Normal (10th–90th percentile), thin (<10th percentile), and thick (>90th percentile). The outcomes of the newborns were evaluated after delivery and statistical analysis was conducted using ANOVA to calculate descriptive measures such as the mean and standard deviation. Results: Among the 400 patients at 32 weeks, PT measurements had varied from 25 to 40 mm, with a PT (mean) of approximately 31 mm ± 3.13 mm. At 36 weeks, among the 375 patients, PT ranged from 27 to 44 mm and a mean PT of approximately 35.2 mm ± 3.27 mm. The correlation of PT and the fetal birth weight was noticeable, with a stronger correlation observed at 36 weeks (r = 0.432) compared to 32 weeks (r = 0.316). Conclusion: The overall thickness of the placenta at 32 and 36 weeks is closely related to the stage of pregnancy and can provide valuable insights into the overall wellness of the newborn. It is important to measure PT along with biometric parameters during ultrasound examinations for pregnant women. In addition, we observed the interaction of different factors, including body mass index and parity.